Interrelationships of Personal Values: A Moderated Mediation Analysis Based on Gender and Age - Romanyuk, Lyudmyla; Романюк, Людмила (My University, 2018)
The present study describes ten personal values expressed by men and women from two countries, and it explores the relationships between two opposing values, Achievement and Benevolence, specifying Stimulation as a mediator between them. It is further explored whether such a mediation model could be further qualified by age and Gender as moderators. The 40-item Portraits Values Questionnaire (PVQ), measuring ten basic values, was administered to 1,000 young adults from two countries. Hierarchical regression methods were applied to examine mediation and moderation mechanisms.Minor gender and country differences emerged for some of the ten basic values. An indirect relationship among the three selected values was identified. Stimulation was found to operate as a mediator between achievement and benevolence. A conditional process model was established with Gender moderating the Achievement – Stimulation path (men had a steeper slope than women), whereas age moderated the Stimulation – Benevolence path (younger individuals had a steeper slope than older ones). Gender also moderated the Achievement – Benevolence path (men had a steeper slope than women). For men, the association between achievement and stimulation was stronger than for women. For the younger persons, the association between stimulation and benevolence was stronger than for older ones. For women, the level of benevolence was independent of their achievement level. The present analyses shed new light on indirect and differential associations among personal values, adding a novel perspective to research on cognitive mechanisms involved in the ten basic values’ becoming. Дослідження описує десять особистих цінностей, виражених чоловіками та жінками з двох країн, а також взаємозв’язок між двома протилежними цінностями: досягненням і доброзичливістю, визначаючи стимуляцію як медіатора між ними. Автор з’ясовує, чи може така модель медіації ще більше кваліфікуватись за віком та гендером як модераторами. Для вимірювання десяти основних цінностей 1000 молодих людей із двох країн використано Опитувальник портретів цінностей із 40 пунктів (PVQ). Для перевірки механізмів медіації та модерації застосовано ієрархічні регресійні методи. Менші гендерні та національні відмінності виникли за деякими з десяти основних цінностей. Виявлено непрямий зв’язок між трьома вибраними цінностями. Установлено, що стимуляція діє як медіатор між досягненнями та доброзичливістю. Модель умовного процесу була встановлена з гендером, що моделювала зв’язки досягнення–стимуляція (чоловіки мали міцніші звязки, ніж жінки), тоді як вік модерував шлях стимуляції–доброзичливості (у молодших людей виявлено міцніший зв’язок, ніж у старших). Гендер також моделював зв’язок досягнення–доброзичливість (чоловіки мали міцніші зв’язки, ніж жінки). Для чоловіків зв’язок між досягненням та стимуляцією був більш значущий, ніж для жінок. Для молодших людей зв’язок між стимуляцією та доброзичливістю був більш значущий, ніж для старших. Для жінок рівень доброзичливості виявився незалежним від рівня досягнень. Здійснений аналіз проливає нове світло на непрямі та диференційовані асоціації серед особистих цінностей, додаючи нову перспективу для дослідження когнітивних механізмів, задіяних у становленні десяти основних цінностей.
Взаємозв’язки особистих цінностей: аналіз змодерованої медіації за гендерною та віковою ознаками
Keywords: values; achievement; benevolence; stimulation; gender; age; moderation; mediation; цінності; досягнення; доброзичливість; стимуляція; гендер; вік; модерація; медіація